Soluble Biomarkers associated with chronic lung disease in older children and adolescents with perinatal HIV infection - Hameiri-Bowen, Dan (AIDS, 2021)
OBJECTIVE: HIV-associated chronic lung disease (HCLD) is a common comorbidity in children and adolescents in sub-Saharan Africa (SSA). The pathogenesis of HCLD is unclear and may be driven by underlying dysregulated systemic immune activation and inflammation. We investigated the association between twenty-six plasma soluble biomarkers and HCLD. DESIGN: Case-control analysis of baseline biomarker data from 336 children and adolescents (6-19 years old) with perinatal HIV infection (PHIV) and HCLD (cases) and 74 age and sex-matched controls with PHIV but no CLD. HCLD was defined as having a forced expiratory volume in one second (FEV1) z-score <−1 with no reversibility. METHODS: Cryopreserved plasma collected at recruitment was used in a multiplex bead assay (Luminex) to measure baseline levels of soluble biomarkers. Logistic regression alongside data-reduction and techniques quantifying the interconnectedness of biomarkers were used to identify biomarkers associated with odds of HCLD. RESULTS: Biomarkers of general immune activation and inflammation (β2M, CRP, sCCL5, GCSF, IFN-γ, IP-10), T-Cell activation (sCD25, sCD27), platelet activation (sCD40-L), monocyte activation (sCD14), coagulation (D-Dimer), cellular adhesion (E-selectin), and extracellular matrix degradation (MMP-1, MMP-7, MMP-10) were associated with increased odds of HCLD. Exploratory PCA and assessment of biomarker interconnectedness identified T-cell and platelet activation as centrally important to this association. CONCLUSIONS: HCLD was associated with a large number of soluble biomarkers representing a range of different pathways. Our findings suggest a prominent role for T-cell and platelet activation in HCLD.